(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the poems included in this article, the words that express concepts related to the terms religion and mysticism are lexemes such as may, maichona, wine, kaba, Saki, jomu jam, Muslim, Paradise, hell, repentance, Ghul, rind, porso, hermit, Messiah, dinpaymo, tarso, sanam, butchona kafir, zunnor.It also refers to the functional-semantic properties of similar words.